The Implementation of Communicative Language Teaching: Does It Statistically Enhance Students’ Speaking Skills? - Tuhawiyur Rohmana Al Chothob; Albert Efendi Pohan; Sholahuddin; Adam (JELLT (Journal of English Language and Language Teaching), 2025)
Abstract This study investigates speaking challenges among students and evaluates the effectiveness of Communicative Language Teaching (CLT) in addressing these issues. Conducted at Andalusia Islamic School, the study involved 20 junior high school students. Employing a quantitative approach, data were collected through direct observation and analyzed using SPSS version 20. The research identified key problems, including insufficient vocabulary, low self-confidence, and inadequate practice. Following the application of CLT, there was a notable improvement in students' speaking abilities, with average scores rising from 63 to 70. Significant enhancements were observed in pronunciation, vocabulary, and fluency. This study highlights the effectiveness of CLT in improving speaking skills and offers recommendations for additional support to further enhance student performance. Keywords: Communicative Language Teaching; Speaking Skills; Vocabulary; Fluency; Pronunciation; Self-Confidence)